Analisis Fenomena Fear Of Missing Out (FOMO) Dalam Perspektif Islam - Annisa Silvia Silitonga; Jihan Safira; Muhammad Tegar Dwihadi; Nabila Az'Zahra; Nindya Fahira (Albayan Journal of Islam and Muslim Societies, 2026)
This study examines the phenomenon of Fear of Missing Out (FOMO) from an Islamicperspective amid the rise of social media in the digital age. The objectives of this study are to analyze the FOMO phenomenon, identify its impact on individuals’ social and psychological lives, and explore Islamic perspectives along with solutions that can beapplied in daily life. The study employs a qualitative descriptive method using a literaturereview approach, analyzing verses from the Qur’an, hadiths, books, scientific journals,and previous research relevant to the FOMO phenomenon and the Islamic perspective. The findings indicate that FOMO can trigger stress, social anxiety, social mediadependency, and reduced individual productivity. From an Islamic perspective, FOMO is linked to a lack of gratitude and contentment within a person. This study also emphasizes the importance of self-control, gratitude, and the wise use of social media tomaintain a balance between digital and real life.